Cross-sectional study on the association between neutrophil-percentage-to-albumin ratio (NPAR) and prevalence of stroke among US adults: NHANES 1999–2018 - Chenglin Ye; Yong Mo; Tiansheng Su; Guangxiang Huang; Jiachao Lu; Shuling Tang; Qianrong Huang; Qiuyun Li; Qian Jiang; Fangzhou Guo; Pinghua Wu; Guozhong Zhang; et al. (Frontiers in Neurology)
The neutrophil-to-albumin ratio (NPAR) is a relatively novel composite biomarker of inflammation, which has been used for prognostication in cardiovascular diseases and may also be associated with stroke. A cross-sectional analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018, including 48,734 individuals with complete NPAR and stroke data. The association between stroke prevalence and NPAR values was assessed through multivariate regression analysis. The relationship between these variables was further visualized using restricted cubic splines (RCS). Additionally, potential factors influencing this relationship were explored through subgroup analysis. The regression model revealed a significant association between NPAR and stroke prevalence, even after adjusting for other covariates [1.06 (1.04, 1.08)]. Stroke prevalence was 62% higher in the highest NPAR group compared to the lowest [1.62 (1.40, 1.89)]. The RCS analysis further confirmed this positive correlation. Subgroup analysis showed that this association was not significantly influenced by other factors. This study establishes a strong association between NPAR and stroke prevalence. However, further studies are needed to clarify the underlying mechanisms and establish a direct causal link.